FEEDING STRATEGIES ON CLIMBING PERCH (Anabas testudineus) LARVAE FED WITH NATURAL FOOD - Try Wahyudi; Nuraini '; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
A research was conducted from 3 Desember 2014 to 1 January 2015 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Science, University of Riau. This the growth and survival rate of Climbing Perch larvae (Anabas testudineus), fed on the natural food combinated such as Artemia naupli, water flea and Tubifex sp. The container used was 18 unit, 30x30x30 cm aquarium. The research method was experimental design with a completely randomized design (CRD) with six treatments and three replications. The treatment were A1T3 (one week given the Artemia sp and three week of the Tubifex sp). A2T2 (two week given Artemia sp and two week of the Tubifex sp). A3T1 (three week given Artemia sp and one week of the Tubifex sp). WF1T3 (one week given water flea and the three week of the Tubifex sp). WF2T2 (two week given water flea and two week of the Tubifex sp). WF3T1 (three week given water flea and one week of the Tubifex sp).The results showed that the A1T3 with the absolute weight growth (1,4850g), weight daily growth (22,55%) and the absolute length growth (40,33mm). The best survival rate in the WF2T2 (63,33%). The average % water temperature, pH and dissolved oxygen 270C, 6 and 4.8 ppm respectively.Keyword : Larvae betok (Anabas testudineus), growth, survival rate